Case Study On The Implementation Of Telemedicine In Health Administration At Lopok Health Center: Challenges And Opportunities - Herni Hasifah; Iga Maliga; Ana Lestari; Hamdin, Hamdin (Jurnal EduHealth, 2024)
Telemedicine is a technology-based healthcare service that allows users to consult with doctors face-to-face or remotely for diagnostic consultations and patient care management. In Indonesia, although still relatively new, the use of telemedicine has been widely adopted by the community. However, there are still some challenges that must be faced by telemedicine service providers, one of which is the uneven Internet access in Indonesia, so several regions have not been able to enjoy this service. The purpose of this study is to identify the challenges and opportunities for the implementation of telemedicine in the Lopok Health Center. This research uses mixed methods research. The sample in this study was 120 respondents. Based on the results of the study, it is known that the respondents' knowledge is in the insufficient category (62.5%), the respondents' attitude is in the inadequate category (54.2%), and the willingness to use telemedicine services is in the unprepared category (65%). Based on the results of the study, it can be concluded that the implementation of telemedicine services has great opportunities and challenges, both from the readiness of users and service providers.